2010
DOI: 10.1007/s11172-010-0098-z
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of polyhalonitrosoarenes with phenylacetylene

Abstract: Phenylacetylene reacts with polyhalonitrosoarenes to give two isomers of 1 phenyl 1,2 bis(2,4,6 trihalophenylnitrono)ethane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…For example, terminal alkynes reacted with nitrosoarenes to afford indole derivatives via 1,4 diradical intermediates . When a bulky 2,6-dihalonitrosoarene is used, an α-styryl cation is produced, which is attacked by another nitrosoarene to provide a dinitrone (Scheme a) . Beside terminal alkynes, the Liu group found that ynamide and propiolate could also react with nitrosoarene to give 2-oxoiminylamide and α-imidoyl nitrone with gold salt as the catalyst (Scheme b–c). , As for the common internal alkyne, fewer examples have been reported due to its relatively lower reactivity compared with the terminal alkyne, ynamide and propiolate.…”
mentioning
confidence: 99%
“…For example, terminal alkynes reacted with nitrosoarenes to afford indole derivatives via 1,4 diradical intermediates . When a bulky 2,6-dihalonitrosoarene is used, an α-styryl cation is produced, which is attacked by another nitrosoarene to provide a dinitrone (Scheme a) . Beside terminal alkynes, the Liu group found that ynamide and propiolate could also react with nitrosoarene to give 2-oxoiminylamide and α-imidoyl nitrone with gold salt as the catalyst (Scheme b–c). , As for the common internal alkyne, fewer examples have been reported due to its relatively lower reactivity compared with the terminal alkyne, ynamide and propiolate.…”
mentioning
confidence: 99%